Study on FGNF/epoxy Composite Fabricated by Using Centrifugal Slurry-Pouring Method - Jamian, Saifulnizan; Razali, Siti Nur Fatihah; Abidin, Mohamad Rusydi Zainal (New Approaches in Engineering Research Vol. 6, 2021)
In this study, functionally graded natural fiber/epoxy (FGNF/epoxy) cylinders hybrid composite were fabricated using casting method. Coir husk and empty fruit bunch (EFB) were two type of natural fiber (NF) used in this study. The mechanical properties and microstructure of the composite was determined. Three different pouring height and compositions of NF were investigated i.e. 150, 250 and 300 mm and sample 1 (80% of epoxy, 10% of coir husk, 10% of EFB), sample 2 (80% of epoxy, 15% of coir husk, 5% of EFB) and sample 3 (80% of epoxy, 5% of coir husk 15% of EFB), respectively. As for comparison, epoxy cylinders contain 100% of epoxy was fabricated (sample 4). To characterize the FGNF/epoxy cylinders fabricated, the hardness, density and compression test were carried out. From the observation, it is found that the NF particles can be graded from upper to lower surface of the FGNF/epoxy cylinders by casting. Many NF particles concentrated at the middle and bottom part rather than at the top part of composite. The hardness and density test results show that the hardness and density value along the cylinder vary from the highest value at the lower surface to the lowest value at the upper surface due to the differences of NF composition along the cylinder. Due to difference in density of NF causes the natural fiber particles move to downward by gravity during casting. The compression test result show that sample 1 and sample 2 has recorded the highest and the lowest Young’s modulus, respectively. The Young’s modulus and yield strength of FGNF/epoxy is higher than pure epoxy cylinder composite. It appears that FGNF/epoxy with a gradient in NF composition is superior to the homogeneous composite.